Clinical significance of high monocyte counts for the continuous treatment with nintedanib - Shingo Tsuneyoshi; Yoshiaki Zaizen; Masaki Tominaga; Goushi Matama; Shushi Umemoto; Shuuhei Ohno; Reiko Takaki; Ryo Yano; Kenta Murotani; Masaki Okamoto; Tomoaki Hoshino (BMC Pulmonary Medicine, 2023)
Abstract Background Nintedanib is now widely used to treat interstitial lung disease (ILD). Adverse events, which occur in not a few patients, make it difficult to continue nintedanib treatment, but the risk factors for adverse events are not well understood. Methods In this retrospective cohort study, we enrolled 111 patients with ILDs treated with nintedanib and investigated the factors involved in starting dosage reduction, withdrawal, or discontinuation within 12 months, even with appropriate symptomatic treatment. We also examined the efficacy of nintedanib in reducing the frequency of acute exacerbations and the prevention of pulmonary function reduction. Results Patients with high monocyte counts (> 0.454 × 109/L) had a significantly higher frequency of treatment failure, such as dosage reduction, withdrawal, or discontinuation. High monocyte count was as significant a risk factor as body surface area (BSA). Regarding efficacy, there was no difference in the frequency of acute exacerbations or the amount of decline in pulmonary function within 12 months between the normal (300 mg) and reduced (200 mg) starting dosage groups. Conclusion Our study results indicate that patients with higher monocyte counts (> 0.454 × 109/L) should very careful about side effects with regard to nintedanib administration. Like BSA, a higher monocyte count is considered a risk factor for nintedanib treatment failure. There was no difference in FVC decline and frequency of acute exacerbations between the starting doseage of nintedanib, 300 mg and 200 mg. Considering the risk of withdrawal periods and discontinuation, a reduced starting dosage may be acceptable in the patients with higher monocyte counts or small body sizes.